CRISPR/Cas9-mediated knockout of STAT1 in porcine-derived cell lines to elucidate the role of STAT1 in autophagy following classical swine fever virus infection - Zhang, Liyuan; Liang, Dongli; Min, Kaijun; Liang, Jiaxin; Tian, Yu; Liu, Cheng; Luo, Ting Rong; Li, Xiaoning (Frontiers in Immunology, 2024)
Signal transducer and activator of transcription 1 (STAT1) plays a critical role in immune response, human STAT1 as a transcriptional suppressor of autophagy genes and autophagic activity. Classical swine fever virus (CSFV)-infected induce autophagy, leading to immune evasion. However, there are limited reports on the function of porcine STAT1 in autophagy during CSFV infection. There is also lack of suitable in vitro models for studying porcine STAT1. The objective of this study was to establish porcine PK-15 STAT1-/- and 3D4/21 STAT1-/- cell lines using the CRISPR/Cas9 system to investigate the function of the STAT1 in autophagy. The PK-15STAT1-/- and 3D4/21STAT1-/- cell lines, featuring homozygous knockout of STAT1 gene were successfully constructed using the CRISPR/Cas9 editing system. The knockout efficiency determined to be 82.4% and 81.1%, respectively. Infection with CSFV in porcine PK-15STAT1-/- and 3D4/21STAT1-/- cells led to an observable increase in autophagosomes as evidenced by transmission electron microscope. Additionally, STAT1 knockout (STAT1-/-) by the CRISPR/Cas9 system upregulated the expression of ULK1, Beclin1, and LC3 genes, thereby enhancing autophagy during CSFV infection. Conversely, overexpression of STAT1 downregulated the expression of ULK1, Beclin1, and LC3 genes, leading to inhibition of autophagy during CSFV infection.The application of an autophagy dual-fluorescent-tracking plasmid demonstrated that STAT1 knockout enhanced autophagy accumulation during CSFV infection, while STAT1 overexpression inhibited it. Moreover, the 3D4/21STAT1-/- cell line proved to be a more suitable in vitro model compared to the PK-15STAT1-/- cell line for elucidating the involvement of STAT1 in autophagy during CSFV infection.